Polymerization in surfactant liquid crystalline phases - Wadekar, M. N.; Pasricha, R.; Gaikwad, A. B.; Kumaraswamy, Guruswamy (Chemistry of Materials, 2005)
We report the formation of cross-linked polysiloxane particles having rodlike and sheetlike morphologies by condensation of monomers in organized liquid crystalline mesophases of nonionic surfactants. The characteristic diffraction pattern obtained from the liquid crystalline surfactant assembly is preserved during polymer synthesis. The polymer colloids are rodlike when synthesized in a hexagonal mesophase and are sheetlike when synthesized in a lamellar mesophase. Interestingly, the size of the polymer particles is on the order of micrometers, viz. 3 orders of magnitude larger than the characteristic size of the surfactant mesophase. Thus, the polymers phase separate from the liquid crystalline phase during polymerization, and organize to resemble the mesophase geometry. The polymer particles are organized so as to minimize the elastic distortion of the surfactant mesophase after they phase separate. We speculate that the observed particle morphologies are formed due to the slow kinetics of polycondensation under our experimental conditions.